2015
DOI: 10.1093/eurpub/ckv027
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national trends in perceived school pressure by gender and age from 1994 to 2010

Abstract: Factors associated with child development and differences in societal expectations and structures, along with the possible, albeit, differential impact of the Programme for International Student Assessment (PISA), may partially explain the differences and trends found in school pressure. School pressure increases alongside the onset of adolescence and the shift from elementary school to the higher demanding expectations of secondary education. Time-related increases in school pressure occurred in the years fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 18 publications
7
76
1
3
Order By: Relevance
“…The increase of PSC in teenagers is in line with many other studies, in the Nordic countries as well in most of the Western world, [38][39][40]47] as is the gender difference. [48] It is perhaps not expected that the increase happens in conjunction with improved family economy, but it is not a new phenomenon.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The increase of PSC in teenagers is in line with many other studies, in the Nordic countries as well in most of the Western world, [38][39][40]47] as is the gender difference. [48] It is perhaps not expected that the increase happens in conjunction with improved family economy, but it is not a new phenomenon.…”
Section: Resultssupporting
confidence: 89%
“…Other studies, both from the Nordic countries and elsewhere, have shown that social capital in the family, at school and in the neighborhood has a positive influence on the children's health and wellbeing. [7,37,38,49] The study supports conclusions from other studies stating that a general economic growth is not enough for the wellbeing of the population. It also supports the importance of the social cohesion, affiliation and solidarity, advanced and reinforced by equal distribution of the wealth.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This exposure to academic demands facilitates learning and developments, but may also be a source of stress during adolescence. An international comparative survey showed a marked increase in school stress in the transition through adolescence (Klinger et al, 2015). It also showed consistent gender and age differences over time.…”
Section: Introductionmentioning
confidence: 94%